1970
DOI: 10.1079/bjn19700092
|View full text |Cite
|
Sign up to set email alerts
|

Production, absorption, distribution and excretion of vitamin B12in sheep

Abstract: I. The efficiency of production and utilization of vitamin BIZ was studied with sheep given a cobalt-deficient diet with and without supplementary Co (I mg/d). Vitamin B,, to lignin ratios in rumen contents were used to estimate minimum rates of production and these were related to faecal and urinary excretion. Tissue distribution and excretion of vitamin Blz were studied with [58Co]cyanocobalamin and ~'-deoxyadenosyl[60Co]cobalamin.2. Labelled Co was rapidly sequestered by particulate material in the rumen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
1
1

Year Published

1971
1971
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 29 publications
6
46
1
1
Order By: Relevance
“…Mo levels are least tolerated by cattle, followed by sheep, but are tolerated by goats (Haenlein and Anke 2011). Concentrations of vitamin B12 rise in times of Co supply and fall during periods of dietary deficiency, because Co is needed for the production of vitamin B12 by ruminant bacteria (Smith and Marston 1970;Suttle 2005). Beside all these factors, which have an impact on the concentration macrominerals and trace elements in body tissues, the reliability of reference values is another variable which warrants discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Mo levels are least tolerated by cattle, followed by sheep, but are tolerated by goats (Haenlein and Anke 2011). Concentrations of vitamin B12 rise in times of Co supply and fall during periods of dietary deficiency, because Co is needed for the production of vitamin B12 by ruminant bacteria (Smith and Marston 1970;Suttle 2005). Beside all these factors, which have an impact on the concentration macrominerals and trace elements in body tissues, the reliability of reference values is another variable which warrants discussion.…”
Section: Discussionmentioning
confidence: 99%
“…After perfusing the rumen and the small intestine of fed sheep with blood from other sheep and measuring changes in concentrations of vitamin B 12 in blood after 2 h of perfusion, Rérat et al (1958a) did not demonstrate absorption of vitamin B 12 through the rumen wall, but showed absorption in the distal small intestine. Similarly, from the distribution of a radioactive dose of vitamin B 12 , Smith and Marston (1970) concluded that in sheep, the site of absorption of vitamin B 12 is the small intestine although they measured an important accumulation of vitamin B 12 in the rumen wall. However, using measurements of blood enrichment in the vitamin, Rérat et al (1958b) showed some absorption of vitamin B 12 through the rumen wall when the vitamin solution was placed in the empty rumen of sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the rumen wall could retain the vitamin and release it later into the blood or the rumen cavity (Rérat et al 1958b). Similarly, Smith and Marston (1970) failed to detect vitamin B 12 absorption from the rumen of sheep, but they also observed an accumulation of vitamin B 12 in the rumen wall. To our knowledge, there is no information in the literature on the fate of folic acid in the gastrointestinal tract of sheep.…”
mentioning
confidence: 98%
“…However, the proportion of dietary cobalt used for these synthetic processes is relatively low in sheep and cows, varying from 3% to 15% (Smith and Marston, 1970;Stemme et al, 2008;Girard et al, 2009b). In vitro studies demonstrated that addition of different bases to the culture media enhanced the synthesis of the corresponding cobamides at the expense of the other forms (Ford et al, 1955;Gawthorne, 1970b).…”
Section: Introductionmentioning
confidence: 99%
“…Efficiency of cobalt utilization in the present study was lower than expected. Indeed, in sheep, efficiency of cobalt utilization decreased as the dietary concentration of cobalt increased (Smith and Marston, 1970). In cows fed different diets, efficiency of cobalt utilization for CBL synthesis in the rumen has been reported to be 7.1%, 9.5% and 4.4% for diets providing 0.17, 0.29 and 2.5 mg of Co/kg of DM, respectively (Stemme et al, 2008;Girard et al, 2009a).…”
mentioning
confidence: 99%